Pengembangan Media Lift The Flap Book Berbasis Whole Language dalam Pembelajaran Menyusun Kosa Kata Baru Siswa Kelas II UPT SD Negeri 2 Kelara Kabupaten Jeneponto - Yul Hidayanti M, Rahmi; Bahri, Aliem; Khadijah Razak, Nur (AIJER: Algazali International Journal Of Educational Research, 2025)
This study aims to enhance the acquisition of new vocabulary and improve the students' knowledge in constructing new vocabulary among second-grade students at Public Elementary School 2 Kelara, Jeneponto Regency, through the use of Lift-the-Flap Book media based on the Whole Language approach. This research is categorized as a development study. The research procedures include a preliminary study and information gathering, planning, development of the initial product format, initial field testing, first product revision, operational testing, and final product revis. The subjects of this study were second-grade students at Public Elementary School 2 Kelara, Jeneponto Regency. The results showed that the use of the media was effective in supporting students in constructing new vocabulary. This effectiveness is reflected in the increase in the students’ average scores, where the pre-test score of 57.5 rose to 83.3 in the post-test, representing an average improvement of 25.8 points. Based on these findings, it can be concluded that the use of Lift-the-Flap Book media based on the Whole Language approach is highly valid, practical, and effective in improving both the acquisition and construction of new vocabulary among second-grade students at Public Elementary School 2 Kelara Jeneponto Regency.